The first report of chickpea (Cicer arietinum L.) tolerance to Paraquat in Australia - Mahajan, Gulshan; Chauhan, Bhagirath S. (Frontiers in Agronomy, 2022)
Chickpea growers in Australia have no post-emergent (POST) herbicides labeled for broadleaf weed control and they rely on pre-emergent herbicides for control of broadleaf weeds. Crop losses may occur when pre-emergent herbicides perform poorly and are unable to provide effective weed control. Chickpea tolerance to POST application of paraquat was tested in this study. Paraquat (180 g ai ha-1) applied POST (up to 10 days after crop emergence) did not injure chickpeas and reduce plant height, and biomass when compared with nontreated control. When the crop just emerged, even the highest dose of paraquat (540 g ai ha-1) did not cause any injury or reduce chickpea biomass compared with nontreated control. Moderate toxicity to chickpea at paraquat 360 or 540 g ai ha-1 was observed when applied 20 days after crop emergence. This study suggests that paraquat POST has the potential to provide broad-spectrum weed control, including broadleaf weeds at an early stage of chickpea. However, the potential for crop injury to paraquat at higher doses, especially when applied at a late stage of the crop warrants further evaluation under field conditions. The study also suggests that tank mix applications of paraquat with residual herbicides may be useful for season-long weed control in chickpea and result in improved yield, therefore, warranting further evaluation of the tank-mix application of paraquat with pre-emergent herbicides for season-long weed control under field conditions.